Poverty in Nepal (Economic Journal of Nepal, 2014)
Nepal is one of the poorest countries in the world with stratified society. Although the incidence has decreased, absolute number of poor living below the poverty line has increased sharply. The methodological adjustments has underestimated the poverty incidence under Nepal Living Standard Survey round second and third (NLSS II & III).Therefore, the study concludes thatthe population living below poverty line in Nepal is at increasing trend but the intention of the government seems to show decreasing trend by adjusting it in different ways. Adoption of the New Economic Polices is one of the major reasons for increasing the problem of poverty, rural-urban differences and social tension in Nepalese society.